Employers’ experience in managing high potential employees in Malaysia - Juhdi, Nurita; Pa’wan, Fatimah; Hansaram , Rammilah (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to determine key competencies used by organizations in identifying high potential employees. It also seeks to examine practices and programs to manage such employees and finally to identify problems encountered in the development programs. Design/methodology/approach – The respondents of the study were HR practitioners. Convenient sampling was used and the respondents answered survey forms that were sent out using regular mails and e-mails. As a result, 237 forms were generated and used for analyses. In order to test construct validity, factor analyses were performed and mean values of each variable were also used for interpretations. Findings – Employers put highest emphasis on employees who were customer service oriented. Three major competences were identified – results-oriented character, interpersonal competence and technical competence/flexibility. The most common method to identify potential was performance appraisal by immediate superiors. The most common method to develop high potential employees was job enlargement and the most common problem in the development programs was in dealing with those who had personal and work-life balance. Practical implications – Performance appraisal done by immediate supervisor may not be the best method to gauge future performance and should be coupled with performance review or discussion with the superiors. Job experience is still effective in developing potential. Specific policies that help employees to balance personal and work life are important in development programs. Originality/value – The responses from the HR practitioners shed some lights on what major competences are important in identifying potential that can be used in talent management.